Fungal-mediated lung allergic airway disease: The critical role of macrophages and dendritic cells. - Julio Furlong-Silva; Peter Charles Cook (PLoS Pathogens)
Fungi are abundant in the environment, causing our lungs to be constantly exposed to a diverse range of species. While the majority of these are cleared effectively in healthy individuals, constant exposure to spores (especially Aspergillus spp.) can lead to the development of allergic inflammation that underpins and worsen diseases such as asthma. Despite this, the precise mechanisms that underpin the development of fungal allergic disease are poorly understood. Innate immune cells, such as macrophages (MΦs) and dendritic cells (DCs), have been shown to be critical for mediating allergic inflammation to a range of different allergens. This review will focus on the crucial role of MΦ and DCs in mediating antifungal immunity, evaluating how these immune cells mediate allergic inflammation within the context of the lung environment. Ultimately, we aim to highlight important future research questions that will lead to novel therapeutic strategies for fungal allergic diseases.